2018
DOI: 10.3390/microorganisms6040123
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Posaconazole and Amphotericin B in the Treatment of Candida glabrata Biofilms

Abstract: Candidemia cases have been increasing, especially among immunosuppressed patients. Candida glabrata is one of the most resistant Candida species, especially to the azole drugs, resulting in a high demand for therapeutic alternatives. The minimum inhibitory concentration (MIC), minimum fungicidal concentration (MFC), and minimum biofilm eradication concentration (MBEC) were determined for posaconazole (Pcz) and amphotericin B (AmB). The drug combinations of both drugs were evaluated on pre-formed biofilms of C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 66 publications
2
16
0
Order By: Relevance
“…Therefore, this high suffering of drug resistance has been attributed to the no synergy. Rodrigues et al have also tried combining two common antifungal drugs (AMB and posaconazole), and the FICI showed that the combination did not bring a clear advantage for this species [44]. Also, in agreement with our results, other studies notably confirmed the antifungal effects of farnesol against Candida species.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, this high suffering of drug resistance has been attributed to the no synergy. Rodrigues et al have also tried combining two common antifungal drugs (AMB and posaconazole), and the FICI showed that the combination did not bring a clear advantage for this species [44]. Also, in agreement with our results, other studies notably confirmed the antifungal effects of farnesol against Candida species.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the combinations of fluconazole and amphotericin B mainly showed indifferent interactions in terms of effects against C. tropicalis (70.6%) and C. parapsilosis (50%) isolates, but antagonistic interactions were observed against the two Candida species isolates. Rodrigues and colleagues showed indifference effects for the voriconazole–amphotericin B combination against C. glabrata [36].…”
Section: Discussionmentioning
confidence: 99%
“…To determine the minimal antifungal concentration that decreases at least 2 log of biofilm, 200 µL -1 of PBS (pH 7.5) was first added to each well of the 96-well microplate containing biofilm specimens 16 . The plate was then subjected to sonication using an ultrasonic bath for 5 min at 36 ºC and 40 kHz (Sanders Medical, MG, Brazil), disrupting the biofilm matrix cells through cavitation.…”
Section: Determination Of Minimum Biofilm Eradication Concentration (...mentioning
confidence: 99%
“…After incubation (24 h at 36 °C), the CFU number was determined, and CFU per area unit (Log 10 CFU/cm 2 ) was calculated. A strong reduction in biofilm was considered when > 2log CFU/cm 2 , as previously described 16 .…”
Section: Determination Of Minimum Biofilm Eradication Concentration (...mentioning
confidence: 99%